2002
DOI: 10.1109/tnano.2002.1005425
|View full text |Cite
|
Sign up to set email alerts
|

The "millipede" - nanotechnology entering data storage

Abstract: We present a new scanning-probe-based data-storage concept called the "millipede" that combines ultrahigh density, terabit capacity, small form factor, and high data rate. Ultrahigh storage density has been demonstrated by a new thermomechanical local-probe technique to store, read back, and erase data in very thin polymer films. With this new technique, nanometer-sized bit indentations and pitch sizes have been made by a single cantilever/tip into thin polymer layers, resulting in a data storage densities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
521
0
7

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 702 publications
(535 citation statements)
references
References 27 publications
5
521
0
7
Order By: Relevance
“…Fewer studies have focused on the hydrodynamic interaction of multiple beams vibrating in close proximity. Cantilever arrays are encountered in applications such as the IBM millipede (Vettiger et al 2002) and when mimicking the beating wings of insects (Lehmann et al 2005). Hosaka and Itao (2002) investigated the interaction between two cantilevers oriented such that the lengthwise-edges came in contact when the gap was zero, an orientation which will be referred to in this paper as "edge-to-edge."…”
Section: Introductionmentioning
confidence: 99%
“…Fewer studies have focused on the hydrodynamic interaction of multiple beams vibrating in close proximity. Cantilever arrays are encountered in applications such as the IBM millipede (Vettiger et al 2002) and when mimicking the beating wings of insects (Lehmann et al 2005). Hosaka and Itao (2002) investigated the interaction between two cantilevers oriented such that the lengthwise-edges came in contact when the gap was zero, an orientation which will be referred to in this paper as "edge-to-edge."…”
Section: Introductionmentioning
confidence: 99%
“…If is the sector number, the sector is allocated in data allocation round and in position of the corresponding column of , which is given by (10) The first field to store symbols of each codeword of sector is (11) whereas the first field to store symbols of each codeword of sector is given by (12)…”
Section: A Number Of Symbols Per Storage Fieldmentioning
confidence: 99%
“…However, the data rates that can be achieved by a single AFM probe are not competitive with current magnetic-recording technologies. One solution to achieve a higher total data rate is the use of arrays of probes operating in parallel [11]. In this case, each probe performs read/write/erase operations on a dedicated area, named a storage or data field, while the storage medium is placed in the -plane.…”
Section: Introductionmentioning
confidence: 99%
“…However, its slow scan speed considerably limits the throughput. It has been shown that this can be overcome by parallel operation of large probe arrays [1,2]. Integrated functionality such as the nanometer scale detection of cantilever deflection will greatly simplify the operation of large 2D probes.…”
Section: Introductionmentioning
confidence: 99%